(3QGTjcGJ GdgfOs - (3eMeO Hf CMeO, CHh GdQjMGf GdHjQhfj GdNhGQRej,J (B440 (3g` s ((3GdehUd s)
(3ChdgG (B:s
(3GdfSHI ajeG Hjf GdebGOjQ GdeJLGfSI gi UhQI ef UhQ GdEVGaGJ jMUd dgG ef LgI GdcejI s
(3BNQgG (B:s
(3hCXf Cfi CJjJ Ydi eGJVefg GdebGd hCSJhajJg s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B241s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B475 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjGVjGJ (B- (3bSe (B3 - (3U (B45 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdQjGVjGJs